The customers satisfaction on retailers’ brand products: a study on selected areas in Klang Valley - M. Zain, Osman; Saidu, Mohammed Bashir (2016)
In recent years, there has been a shift from national brand towards retailer's brand. This phenomenon is very obvious in developed nations, while growing increasingly in developing nations, such as Malaysia. This study attempts to uncover the customers’ acceptance, and identify factors deemed important in influencing this satisfaction. The literature review was conducted to compile research results conducted in Western nations. Based on this literature review, a research model was proposed that comprises customer satisfaction, product quality, product price, product promotion, and product risk. Using the systematic random intercept approach at the Malls, sample size of 206 was used in this study. The results of the study support past study in the developed nations whereby there exist significant relations between customers’ satisfaction and the other four factors. All the four factors identified by past study also have significant influence on customers’ satisfaction with the retailers’ retailer's brand products.